Archaeal Sources of Intact Membrane Lipid Biomarkers in the Oxygen Deficient Zone of the Eastern Tropical South Pacific - Sollai, Martina; Villanueva, Laura; Hopmans, Ellen C.; Keil, Richard G.; Sinninghe Damsté, Jaap S. (Frontiers in Microbiology, 2019)
Archaea are ubiquitous in the modern ocean where they are involved in the carbon and nitrogen biogeochemical cycles. However, the majority of Archaea remain uncultured. Archaeal specific membrane intact polar lipids (IPLs) are biomarkers of the presence and abundance of living cells. They comprise archaeol and glycerol dibiphytanyl glycerol tetraethers (GDGTs) attached to various polar headgroups. However, little is known of the IPLs of uncultured marine Archaea, complicating their use as biomarkers. Here, we analyzed suspended particulate matter (SPM) obtained in high depth resolution from a coastal and open ocean site in the eastern tropical South Pacific (ETSP) oxygen deficient zone (ODZ) with the aim of determining possible biological sources of archaeal IPL by comparing their composition by Ultra High Pressure Liquid Chromatography coupled to high resolution mass spectrometry with the archaeal diversity by 16S rRNA gene amplicon sequencing and their abundance by quantitative PCR. Thaumarchaeotal Marine Group I (MGI) closely related to Ca. Nitrosopelagicus and Nitrosopumilus dominated the oxic surface and upper ODZ water together with Marine Euryarchaeota Group II (MGII). High relative abundance of hexose phosphohexose- (HPH) crenarchaeol, the specific biomarker for living Thaumarchaeota, and HPH-GDGT-0, dihexose- (DH) GDGT-3 and -4 were detected in these water masses. Within the ODZ, DPANN (Diapherotrites, Parvarchaeota, Aenigmarchaeota, Nanoarchaeota, and Nanohaloarchaea) of the Woesearchaeota DHVE-6 group and Marine Euryarchaeota Group III (MGIII) were present together with a higher proportion of archaeol-based IPLs, which were likely made by MGIII, since DPANN archaea are supposedly unable to synthesize their own IPLs and possibly have a symbiotic or parasitic partnership with MGIII. Finally, in deep suboxic/oxic waters a different MGI population occurred with HPH-GDGT-1, -2 and DH-GDGT-0 and -crenarchaeol, indicating that here MGI synthesize membranes with IPLs in a different relative abundance which could be attributed to the different detected population or to an environmental adaptation. Our study sheds light on the complex archaeal community of one of the most prominent ODZs and on the IPL biomarkers they potentially synthesize.